2007
DOI: 10.1590/s1517-83822007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of antagonistic substance produced by a Clostridium butyricum strain

Abstract: The production of antagonistic substance by bacterium present in the infected root canal system (RCS) probably is an important ecological factor for its successful colonization of the local. The objective of this study was to partially characterize an antagonistic substance produced by a Clostridium butyricum isolated from infected RCS. Production of inhibitory compound was evaluated by the agar double layer diffusion technique using Fusobacterium nucleatum and Bifidobacterium adolescentis as indicator bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several studies have been assayed bacterial antagonistic activity in root canal microbiota (3,21). According to Klaenhammer (14), lactic acid bacteria produce antibacterial substances that vary in their spectrum of activity, mode of action, molecular mass, genetic determinants, and biochemical characteristics.…”
Section: Growth Curves Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been assayed bacterial antagonistic activity in root canal microbiota (3,21). According to Klaenhammer (14), lactic acid bacteria produce antibacterial substances that vary in their spectrum of activity, mode of action, molecular mass, genetic determinants, and biochemical characteristics.…”
Section: Growth Curves Assaymentioning
confidence: 99%
“…Most previous studies examining the ecological complexity of root canal infections have shown antagonistic bacterial activity in these sites (2,3,16,21). The present study…”
Section: Growth Curves Assaymentioning
confidence: 99%
“…1998, Peters et al. 2002, Socransky & Haffajje 2005), are important factors in the establishment and colonization of the root canal (Caires et al. 2007, Sundquivst & Figdor 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2007, Sundquivst & Figdor 2007). Synergism occurs when the metabolism of a species produces nutrients and growth factors that are reliable food sources for another species, whilst antagonism occurs when a microorganism produces substances that may be toxic to or inhibit the growth of another species (Sundqvist 1992, Caires et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation